The Impact of Inductive Teaching on Pre-Tertiary Students’ Academic Performance in Solving Circle Theorem Problems - Gona Akwasi Dimaweh , Thomas; Bonyah, Ebenezer; Adu Obeng, Benjamin (EDUPEDIA Publisher, 2026)
Purpose – This study was motivated by the persistent challenges students face in solving geometry problems, particularly circle theorems. It aimed to investigate how an inductive teaching approach affects pre-tertiary students’ performance in solving circle theorem problems. Methodology – A mixed-methods approach grounded in the pragmatist paradigm was used, adopting a quasi-experimental pre-test–post-test control-group design. Using purposive and stratified sampling, 84 second-year students were selected and assigned to experimental and control groups. The experimental group was taught through the inductive approach, while the control group received conventional instruction. Data were collected through achievement tests and interviews, and analysed using descriptive statistics, t-tests, and thematic analysis. Findings – Students demonstrated significant conceptual, procedural, and factual difficulties in solving circle-theorem problems. However, the experimental group performed significantly better in the post-test than the control group. Interview findings also indicated that students perceived the inductive approach as more engaging, interactive, and effective in improving understanding. The study concluded that the inductive intervention positively influenced both achievement and attitudes toward learning the circle theorem. Novelty – The study’s novelty lies in examining the effect of inductive teaching on students’ performance in solving circle-theorem problems within a pre-tertiary education context. Significance – The study contributes to improving mathematics teaching strategies by emphasizing the potential of inductive teaching to enhance students’ achievement and attitudes toward complex concepts such as circle theorems, thereby supporting wider implementation and future research.